2009
DOI: 10.1681/asn.2008060590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Membrane Permeability on Survival of Hemodialysis Patients

Abstract: The effect of high-flux hemodialysis membranes on patient survival has not been unequivocally determined. In this prospective, randomized clinical trial, we enrolled 738 incident hemodialysis patients, stratified them by serum albumin Յ4 and Ͼ4 g/dl, and assigned them to either low-flux or high-flux membranes. We followed patients for 3 to 7.5 yr. Kaplan-Meier survival analysis showed no significant difference between high-flux and low-flux membranes, and a Cox proportional hazards model concurred. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
280
2
16

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 361 publications
(314 citation statements)
references
References 23 publications
16
280
2
16
Order By: Relevance
“…Increasing dialysis dose beyond these targets does not further improve the nutritional status. Further, most nutritional measures did not differ among patients exposed to highflux compared with low-flux HD membranes (25). The Frequent Hemodialysis Networks trial found no appreciable difference in nutritional markers between patients randomly assigned to in-center HD six times per week versus standard in-center HD three times per week (26).…”
Section: Prevention Of Pew: a Cause-specific Approachmentioning
confidence: 99%
“…Increasing dialysis dose beyond these targets does not further improve the nutritional status. Further, most nutritional measures did not differ among patients exposed to highflux compared with low-flux HD membranes (25). The Frequent Hemodialysis Networks trial found no appreciable difference in nutritional markers between patients randomly assigned to in-center HD six times per week versus standard in-center HD three times per week (26).…”
Section: Prevention Of Pew: a Cause-specific Approachmentioning
confidence: 99%
“…In contrast, significant removal of ␤2M can be established with high-flux HD, because of convective transport by internal filtration within the dialyzer. The Hemodialysis (HEMO) and the Membrane Permeability Outcome (MPO) study showed lower serum ␤2M levels in high-flux HD as compared with low-flux HD patients (4,9). In addition, it has been shown that removal of ␤2M is further increased with online hemodiafiltration (HDF) by using excess ultrafiltration to provide increased convective transport.…”
mentioning
confidence: 99%
“…Moreover, oxidized forms of albumin can lead to an underestimation of the serum albumin level [30], questioning the rationale of the real significance of low serum albumin levels in CKD patients and in the evaluation of their nutritional status. In MPO study [10] , survival of patients with a low serum albumin level was increased with the use of high-flux membranes, while no effect was found in normo-albuminemic patients. As lower level of albumin raise the question of a possible increase in oxidized forms, the better survival could result from a significant removal of toxic forms of albumin by high-flux membranes.…”
Section: How Can Albumin Removal Be Interesting?mentioning
confidence: 94%
“…However, the amount of albumin leak needs to be questioned in regard to the quality of albumin leaked. Interestingly, in MPO study [10] , the use of high-flux membranes was linked with a better survival in the low serum albumin group despite a higher sieving coefficient leading to an increased albumin leak. These facts raised the question of the merit of the specific removal of toxic and dysfunctional forms of albumin in HD ( Fig.…”
Section: Is Albumin Leak Still a Central Issue In The Evaluation Of Dmentioning
confidence: 96%
See 1 more Smart Citation